2003
DOI: 10.1016/s0008-6363(02)00660-0
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 and -3 dissociations from caveolae to cytosol in the heart during aging and after myocardial infarction in rat

Abstract: We demonstrate that dissociation of caveolin from caveolae is associated with aging and heart failure, the process being related to the decreased NOS activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 33 publications
9
82
4
Order By: Relevance
“…In addition, caveolin-1 and -3 dissociation from caveolae occurs during aging, and NOS activity is negatively correlated with caveolin-1 levels in the cytosol. 27 To the extent that aging is associated with decreased caveolarassociated NOS, the effect of exogenous L-arginine could be additionally impaired. With arginase inhibition, L-arginine could restore responsiveness of cytosolic NOS and thus restore vasorelaxation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, caveolin-1 and -3 dissociation from caveolae occurs during aging, and NOS activity is negatively correlated with caveolin-1 levels in the cytosol. 27 To the extent that aging is associated with decreased caveolarassociated NOS, the effect of exogenous L-arginine could be additionally impaired. With arginase inhibition, L-arginine could restore responsiveness of cytosolic NOS and thus restore vasorelaxation.…”
Section: Discussionmentioning
confidence: 99%
“…This roughly corresponds to the patterns seen in staining of the NMJs, because NMJ staining for caveolin-3 in neonates is considerably less intense than in adults (unpublished observations). Ratajczak et al (2003) reported some dissociation of caveolin-3 from sarcolemmal caveolae in aging cardiac muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is warranted in unravelling the roles of caveolae and caveolin-3 in control of cardiomyocyte EGFR signalling. Importantly, significant reductions in myocardial caveolin-3 expression/localisation with ageing (Kawabe et al, 2001;Ratajczak et al, 2003;Peart et al, 2007), infarction (Ratajczak et al, 2003), and disease (Piech et al, 2003;Penumathsa et al, 2008;Crossman et al, 2011;Sharma et al, 2011;Lei et al, 2013) have the potential to dysregulate myocardial EGFR signalling.…”
Section: Cell Membrane Localisation -Membrane Rafts Caveolae and Cavmentioning
confidence: 99%